2012
DOI: 10.3748/wjg.v18.i42.6114
|View full text |Cite
|
Sign up to set email alerts
|

Anemia after gastrectomy for early gastric cancer: Long-term follow-up observational study

Abstract: AIM:To identify the incidence and etiology of anemia after gastrectomy in patients with long-term follow-up after gastrectomy for early gastric cancer. METHODS:The medical records of those patients with early gastric adenocarcinoma who underwent curative gastrectomy between January 2006 and October 2007 were reviewed. Patients with anemia in the preoperative workup, cancer recurrence, undergoing systemic chemotherapy, with other medical conditions that can cause anemia, or treated during follow up with red cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…A long-term follow-up study showed that anemia was common after gastrectomy and increased from 25% at 3 months to 37% at 48 months after surgery, iron deficiency being the major cause [1]. In our study, the incidence of anemia was lower and decreased during follow-up, showing that a close monitoring and appropriate nutritional supplementation can easily prevent the incidence of anemia after gastrectomy.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…A long-term follow-up study showed that anemia was common after gastrectomy and increased from 25% at 3 months to 37% at 48 months after surgery, iron deficiency being the major cause [1]. In our study, the incidence of anemia was lower and decreased during follow-up, showing that a close monitoring and appropriate nutritional supplementation can easily prevent the incidence of anemia after gastrectomy.…”
Section: Discussionmentioning
confidence: 63%
“…Anemia is a frequent complication after total gastrectomy, and deficiencies of iron, VB12, or folate, either alone or in combination, are also common during follow-up [1,12]. Impaired iron absorption is explained by the following mechanisms: bypass of the duodenum, increased intestinal transit time and reduction in gastric acid which is necessary for the absorption of food iron [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In bariatric [13][14][15][16][17] and gastric cancer surgery [18][19][20][21], it has been shown that new micronutrient deficiencies may develop on the long-term or pre-existent deficiencies worsen postoperatively in a considerable number of patients. This effect was most prominent following bariatric Roux-en-Y gastric bypass surgery and total gastrectomy for cancer with Roux-en-Y esophagojejunostomy.…”
Section: Introductionmentioning
confidence: 99%